Strategi Pengembangan Candi Muaro Jambi Sebagai Wisata Religi - Firsty, Ophelia; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 7 No 1 (2019): VOL 7, NO 1 (2019): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2019)
Muaro Jambi temple a largest temple site in Sumatra island, with area of 3981 hectares wide. This temple is a legacy from Srivijaya and Melayu Empires, and a center of Buddhist teaching in 9th to 11th century. Considering history and significances of temple for Buddhists, effective development of religious tourism is required. This research investigate the development strategy in Muaro Jambi Temple as religious tourism. Using descriptive qualitative method, this research will describe the development of temple from various aspects of tourism development. The result of research analysis done by using descriptive qualitative analysis provide result through documentation supported narration. The research result show that tourism development is still in early stage and so problems in various aspects of development are found, with most of them caused by low synergy among the stakeholders. Thus, every stakeholder are expected to increase their synergy and cooperation for the sake of religious tourism growth in Muaro Jambi temple. Key Words : Religious Tourism, Tourism development, Buddhist Temple